Strategi Pengembangan Wisata Kedung Mansur di Desa Jatisari - Yuliana, Siti; Kistanti, Nurjannah Rahayu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This The current tourism phenomenon is experiencing rapid development. Indonesia's rapid economic growth and public awareness of community-based tourism are tourism management concepts that place local communities as key actors in tourism development. This concept aims not only to increase tourist visits but also to empower communities, preserve local culture, and preserve the environment. The development of community-based tourism in Jatisari Village holds significant potential for boosting the local economy and empowering the community. This research was conducted using qualitative methods. Data collection techniques used were observation and interviews. Interviews were conducted with community leaders, tourism operators, and other stakeholders to obtain more in-depth information. The data used included interview results, documentation, and observations. The purpose of this research was to identify potential and obstacles, and formulate appropriate strategies for developing Kedung Mansur tourism using a participatory and sustainable approach so that tourism can develop rapidly and increase its appeal to both local and international tourists. However, several obstacles remain to be addressed to ensure that tourism in Kedung Mansur achieves these goals. This research aims to identify opportunities and obstacles for developing community-based tourism in Jatisari Village.